Fear of crime beyond the walls: Effects of gated communities in neighbouring public spaces. The case of the Greater Metropolitan Area of Costa Rica. - Barrantes Chaves, Karla (2021)
Tesis doctoral de profesora becaria de la Universidad de Costa Rica.